Tectonic evolution and deep mantle structure of the eastern Tethys since the latest Jurassic - Zahirovic, S; Matthews, K; Flament, N; Müller, R; Hill, K; Seton, M; Gurnis, M (Elsevier, 2016)
The breakup of Pangea in the Jurassic saw the opening of major ocean basins at the expense of older Tethyan and Pacific oceanic plates. Although the Tethyan seafloor spreading history has been lost to subduction, proxy indicators from multiple generations of Tethyan ribbon terranes, as well as the active margin geological histories of volcanism and ophiolite obduction events can be used to reconstruct these ancient oceanic plates. The plate reconstructions presented in this study reconcile observations from ocean basins and the onshore geological record to provide a regional synthesis, embedded in a global plate motion model, of the India-Eurasia convergence history, the accretionary growth of Southeast Asia and the Tethyan-Pacific tectonic link through the New Guinea margin.